Diversification of the tourism activity in Antarctica - A. Fedchuk (Ukrainian Antarctic Journal, 2014)
During the last decade, types of tourism and other non-governmental activities in Antarctica have become more diverse. Using the post visits report provided by the International Association of Antarctica Tour Operators, all known examples of activities it was identified and divided over various categories of activities, including modes of transport to Antarctica (sea-based, air-based, and combined tours), on the basis of which develop land-based (onshore and deep inland) tourist expeditions, as well as more specific sports or adventure activities that form part of larger traditional expeditions in the Antarctic. Given the inclusion land-based and adventure tourism as one of the ‘outstanding questions’ within multi-year strategic plan for the Antarctic Treaty Consultative Meetings, it is identified the main issues of the tourism regulation, such as compliance with the current international low regime, co-operation with national Antarctic programs, tourist safety, and environmental protection as well.